The Effect of Sawdust and Cocopeat Planting Media on Root Growth in Grafting of Mahkota Dewa Plants (Phaleria Macrocarpa (Scheff.) Boerl.) - Sari, Poni Delita; Vauzia, Vauzia; Chatri, Moralita; Putri, Irma Leilani Eka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Phaleria macrocarpa (Scheff.) Boerl., referred to as Mahkota Dewa, is a valuable medicinal plant with significant economic importance, requiring effective propagation methods to enhance its cultivation. Grafting is a frequently utilized technique, and its effectiveness is affected by the kind of growth medium used. This study aimed to evaluate the effect of different planting media on root growth of grafted Mahkota Dewa. The research was carried out between January and March 2026 in Lubuk Minturun, employing a Completely Randomized Design (CRD) with three different treatments: soil (P0), sawdust (P1), and cocopeat (P2), each consisting of six replications. The parameters monitored included the number of roots, root length, and dry weight of roots. Data were evaluated by using analysis of variance (ANOVA). The findings showed that the type of growth medium did not have a significant impact (p>0.05) on any of the root growth parameters measured. These results imply that alternative mediums like sawdust and cocopeat can serve as replacements for soil without notably hindering root growth in grafted P. macrocarpa.